Historija je učiteljica života / History is Life's Teacher - Bandžović, Sead (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
This text is the review of a book "Through Prism of History" by Fikret Karčić (Center for Advaced Studies, 2017.).